Structural and magnetic characterization of Mn/NiFe bilayers with ion-beam-assisted deposition. (17th November 2017) - Wu, Chun-Hsien; Zheng, Chao; Chiu, Chun-Cheng; Manna, Palash Kumar; van Lierop, Johan; Lin, Ko-Wei; Pong, Philip W. T.
Abstract: The exchange bias effect in ferromagnetic (FM)/antiferromagnetic (AF) bilayer structures has been widely investigated because its underlying principle is critical for spintronic applications. In this work, the effect of Ar + beam bombardment on the microstructural and magnetic properties of the Mn/NiFe thin films was investigated. The in-situ Ar + bombardment nontrivially promoted the Mn/NiFe intermixing and facilitated the formation of the FeMn phase, accompanied by a remarkable reduction of Mn and NiFe layer thickness. The enhanced Mn/NiFe intermixing greatly disordered the interfacial spins, inhibiting the interfacial exchange coupling and giving rise to a significant decrease of the exchange bias field ( H ex ). The facilitated Mn/NiFe intermixing effect also dramatically degraded the magnetocrystalline anisotropy of the NiFe crystallites, leading to a notable suppression of the coercivity ( H c ). These results indicate that both the exchange bias and coercivity of the Mn/NiFe bilayers can be directly affected by the in-situ Ar + bombardment, offering an effective way to modify the magnetism of the exchange-bias systems.